Measurement by applying internet financial reporting on the level of information presentation in the competitive FinTech peer-to-peer lending industry - Al-Khowarizmi, Al-Khowarizmi; Efendi, Syahril; Nasution, Mahyuddin Khairuddin Matyuso; Mawengkang, Herman (IAES International Journal of Artificial Intelligence (IJ-AI), 2024)
Technological advances in the financial sector can certainly support the business decision-making process. Moreover, digital financial technology such as FinTech is a competitive industry that has both peer-to-peer (P2P) and merchant pillars. The industry must update its business activities through its information media. One of them is internet-based financial reporting or better known as internet financial reporting (IFR). IFR itself is a delivery of financial information that is carried out in real time and can be easily seen by the wider community by using the website as a medium. This study aims to determine whether the application of IFR to FinTech P2P Lending companies in Indonesia has been widely implemented or not. Later the variables used in this study are content, appearance, and timing with a total of 20 indicator variable items to be tested. The results of this paper show that 30 P2P lending FinTech Industries in Indonesia have been able to implement IFR with an average score of 80%. IFR scores obtained by each industry have almost the same value ranging from 65% to 95% with the highest total score of 95% and the lowest score of 65%.